Barriers and facilitators to adherence to Human Immunodeficiency Virus (HIV) Treatment (Research, Society and Development, 2025)
This study aimed to identify the main barriers and facilitators that impact adherence to antiretroviral therapy (ART) among people living with HIV. The research was conducted through a narrative literature review, with searches carried out in the LILACS, SciELO, MEDLINE and Ministry of Health, databases, using standardized descriptors and inclusion criteria related to the topic. Articles published between 2018 to 2024 were selected, totaling 22 studies analyzed The results showed that the most significant barriers to ART adherence include social stigma and discrimination, adverse drug effects, limited access to healthcare services, low educational level, psychoactive substances use, and lack of family support. On the other hand, facilitators identified were strong therapeutic relationships with the healthcare providers, humanized care, psychosocial support, simplified treatment regimens,as well as public policies that ensure free access to treatment and diagnostic tests. It is concluded that adherence to HIV treatment is a complex and multifaceted process that requires interdisciplinary strategies, educational actions, and effective public policies. The nursing professional plays a essential role in this context by delivering comprehensive care, engaging in active listening, and promoting health education.Overcoming barriers and reinforcing facilitators are fundamental to ensure treatment continuity and improve the quality of life of people living with HIV.